Lipid digestion capacity in gilthead seabream (Sparus aurata) from first feeding to commercial size - Arantzamendi, Leire; Roo Filgueira, Francisco Javier; Hernández-Cruz, Carmen María; Fernández-Palacios, Hipólito; Izquierdo, Marisol (Fish Physiology and Biochemistry, 2019)
To characterise the progression of lipid digestion capacity in gilthead seabream across life cycle, the activities of bile salt-activated lipase (BAL) and phospholipase A2 (PLA2) were determined in the digestive tracts of cultured gilthead seabream from first feeding to marketable size (49 μg to 300 g). Four trials were undertaken with gilthead seabream of different ages, fed on diets with fishmeal and fish oil as the main dietary protein and lipid sources and 21–25% lipid contents. Larvae of 4 days after hatching (dah) to 9 dah were fed rotifers with different fatty acid profiles: control (2.8% eicosapentaenoic acid, EPA; 1.6% docosahexaenoic acid, DHA; 5.4% n-3 long-chain polyunsaturated fatty acids, n-3 LC-PUFAs; and 0.2% arachidonic acid, ARA), low EPA (1.38% EPA, 1.6% DHA, 3.9% n-3 LC-PUFA and 0.4% ARA) or low LC-PUFA (0.7% EPA, 1.0% DHA, 1.8% n-3 LC-PUFA and 0.0% ARA) (% dry weight). Larvae fed the low-LC-PUFA diet showed a significantly lower growth at 10 dah. BAL activities were significantly higher in larvae fed the control diet than in those fed low-EPA and low-LC-PUFA diets at 9 dah. BAL activity increased with age across life cycle (49 μg to 300 g). PLA2 activity could not be detected in larvae but increased with age in juvenile and adult gilthead seabream (86 g to 295 g), similar to BAL. Results suggested a correspondence between the stimulation of lipid digestion capacity and growth performance in gilthead seabream by dietary essential fatty acids, particularly by EPA when DHA requirements are met in the diet especially in the very early stages of life cycle, when the progression of BAL and PLA2 activities could be used as indicators of the nutritional status of cultured gilthead seabream larvae. Finally, regarded that PLA2 activity was not detected in 4-dah to 44-dah gilthead seabream larvae, future works are suggested to assess the dietary effect on PLA2 activity and the PLA2 activity pattern along the larval stage of this species using a more sensitive detection method. 484 469 16 0,676 ...